2014
DOI: 10.11604/pamj.2014.17.126.3567
|View full text |Cite
|
Sign up to set email alerts
|

Concordance et apports de l’hystérosalpingographie et de la cœlioscopie dans l’exploration tubaire et pelvienne en cas d’infertilité

Abstract: IntroductionLa coelioscopie et l'hystérosalpingographie sont les deux procédures usuellement admises pour l'exploration tubaire et pelvienne en cas d'infertilité. Les objectifs de ce travail etaient de comparer les données de l'Hystérosalpingographie à celles de la coelioscopie chez des patientes explorées pour infertilité et voir l'apport de l'une par rapport à l'autre.MéthodesEtude prospective menée au service C du centre de maternité et de néonatologie de Tunis, s’étendant sur 15 mois, colligeant 120 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
1
4
1
Order By: Relevance
“…We did the Cohen's kappa test and the correlation between HSG and endoscopy for tubal obstruction in general was 0.36. This result is sensitive and similar to what Mehdi et al reported in his series that was 0.42 [8]. Our study presented a good correlation between HSG and endoscopy in the detection of proximal tubal obstructions with a Cohen's Kappa sensitivity of 0.30.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…We did the Cohen's kappa test and the correlation between HSG and endoscopy for tubal obstruction in general was 0.36. This result is sensitive and similar to what Mehdi et al reported in his series that was 0.42 [8]. Our study presented a good correlation between HSG and endoscopy in the detection of proximal tubal obstructions with a Cohen's Kappa sensitivity of 0.30.…”
Section: Resultssupporting
confidence: 91%
“…Our study presented a good correlation between HSG and endoscopy in the detection of proximal tubal obstructions with a Cohen's Kappa sensitivity of 0.30. Mehdi Kehila et al reported also a significant K-value of 0.48 [8]. The treatment of tubal obstructions is well managed with endoscopy and several techniques have been presented by many authors in the previous literature in order to limit sollicitation of IVF for patients who consult for infertility [12] [13] [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has a diagnostic and possibly therapeutic interest. It is considered by most authors as the "gold standard" in the exploration of the pelvis in cases of infertility [36].…”
Section: Tubal Pathologiesmentioning
confidence: 99%
“…This brings all of the indications for this examination in our study to female infertility as mentioned in the literature. Indeed, hysterosalpingography remains the main indication for exploring tubal pathology and permeability as part of the assessment of primary or secondary infertility [15]. However, it remains of interest during the exploration of certain uterine pathologies and also plays a role in the event of repeated miscarriages (isthmic open bite, malformation).…”
Section: Discussionmentioning
confidence: 99%